1 million trees (and growing) to electrify Yangambi - Center for International Forestry Research (Center for International Forestry Research, 2021)
Since 2018, CIFOR-ICRAF and its partners are promoting forest landscape restoration in Yangambi. Their goal is to bring degraded land back to productivity to create green jobs, reactivate the local economy, enrich soils, and increase energy supply.